The role of Prunus cerasifera Ehrh. in the origin, evolution and improvement of stone fruit cultivars - G. V. Eremin (Труды по прикладной ботанике, генетике и селекции)
At Krymsk Experiment Breeding Station of VIR, as a result of collecting, studying, and selective use of myrobalan plum genetic diversity, the intraspecific taxonomy of the species Prunus cerasifera Ehrh. was clarified. Donors of traits significant for breeding were identified and, with their use, adaptable cultivars of myrobalan plum, Russian plum and clonal rootstocks of stone fruit plants were developed.Intraspecific classification of P. cerasifera is proposed, with the identified subspecies:subsp. cerasifera (typical myrobalan plum);subsp. orientalis (M. Pop.) Erem. et Garcov. (Oriental myrobalan plum);and subsp. macrocarpa Erem. et Garcov. (large-fruited myrobalan plum).Within subsp. P. cerasifera subsp. macrocarpa, varieties were identified:var. macrocarpa (typical, or Krymsk);var. georgica Erem. et Garcov. (Georgian);var. iranica (Koval.) Erem. et Garcov. (Iranian);var. nairica (Koval.) Erem. et Garcov. (Armenian);var. pissardii Carr. (Pissard);and var. taurica (Kost.) Erem. et Garcov. (Taurida).The participation of myrobalan plum in the origin of spp. P. brigantiaca Vill., P. cocomilia Tem., and P. spinosa L. was traced. Involvement of large-fruited myrobalan plum in hybridization with blackthorn contributed to the manifestation of an exceptional polymorphism among the varieties of the hybridogenic species P. domestica L. (P. cerasifera × P. spinosa). As a result of hybridization between myrobalan plum and Chinese plum varieties, a new cultigen species emerged – Russian plum (× P. rossica Erem.). By now, 127 cultivars of this species and 7 clonal rootstocks for stone fruit crops have been developed. These cultivars and clonal rootstocks are zoned for Russia and a number of other countries.